Contrast-Enhanced Ultrasound in the Bladder: Critical Features to Differentiate Occupied Lesions. (12th October 2021) - Liu, Qiping; Gong, Huiling; Zhu, Hui; Yuan, Chunyan; Hu, Bin
Abstract : Objective . To study the clinical diagnostic value of contrast-enhanced ultrasound (CEUS) in bladder occupied lesions. Methods . 38 cases of conventional-ultrasound-found bladder occupied lesions did color Doppler flow imaging (CDFI) and CEUS checks. By comparing the difference between two types of blood flow imaging technologies in displaying the flow of bladder occupied lesions and observing the perfusion modes of contrast agents to enter lesions, the perfusion characteristics of CEUS were analyzed. Finally, they were contrasted with the surgical pathology results. Results . Of all the 38 cases, there were 51 bladder occupied lesions, including 43 bladder malignant tumors, 2 bladder inverted papillomas, and 6 glandular cystitis lesions. The blood flow display rate of bladder occupied lesions was 100% using CEUS. Apparently, it was higher than that of CDFI (62.7%), and the result of these showed a statistically significant difference (P < 0.05 ). Using CEUS, 46 malignant lesions and 5 glandular cystitis lesions were indicated, and the diagnostic accuracy rate was 86.3%. Conclusion . CEUS can improve the blood flow display rate of bladder occupied lesions, and it can also observe the real-time blood flow of these lesions. It can help judge their nature and has a higher clinical value in differentiating the benign from the malignant.